PENGARUH LEVERAGE, NET PROFIT MARGIN, RETURN ON ASSETS, DAN OPERATING PROFIT MARGIN TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Aneka Industri Yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Nugraha, Opanthio; Indrawati, Novita; Hariadi, Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of leverage, net profit margin, return on assets and the operating profit margin on earnings management in various industrial companies listed in Indonesia Stock Exchange in 2012-2014. The population in this research is the company's various industry listed in Indonesia Stock Exchange in 2012-2014 as many as 42 companies. The sampling technique is purposive sampling and obtained a sample of 37 companies. The data collected was secondary data with the method of documentation. Data analysis method used is multiple linear regression analysis. The results of hypothesis testing in showing that the Net Profit Margin, Return on Assets and Operating Profit Margin effect on Earnings Management, while variable Leverage has no effect on Earnings Management.Keyword : leverage, net profit margin,